Apolipoprotein E and Atherosclerosis: From Lipoprotein Metabolism to MicroRNA Control of Inflammation - Laura Bouchareychas; Robert L. Raffai (Journal of Cardiovascular Development and Disease, 2018)
Apolipoprotein (apo) E stands out among plasma apolipoproteins through its unprecedented ability to protect against atherosclerosis. Although best recognized for its ability to mediate plasma lipoprotein clearance in the liver and protect against macrophage foam cell formation, our recent understanding of the influence that apoE can exert to control atherosclerosis has significantly widened. Among apoE’s newfound athero-protective properties include an ability to control exaggerated hematopoiesis, blood monocyte activation and aortic stiffening in mice with hyperlipidemia. Mechanisms responsible for these exciting new properties extend beyond apoE’s ability to prevent cellular lipid excess. Rather, new findings have revealed a role for apoE in regulating microRNA-controlled cellular signaling in cells of the immune system and vascular wall. Remarkably, infusions of apoE-responsive microRNA mimics were shown to substitute for apoE in protecting against systemic and vascular inflammation to suppress atherosclerosis in mice with hyperlipidemia. Finally, more recent evidence suggests that apoE may control the release of microvesicles that could modulate cellular signaling, inflammation and atherosclerosis at a distance. These exciting new findings position apoE within the emerging field of intercellular communication that could introduce new approaches to control atherosclerosis cardiovascular disease.